Developing leadership potential in students using sūrah Yasin: a growth-mindset perspective - Fontaine, Rodrigue Ancelot Harvey (Kulliyyah of Economics, International Islamic University Malaysia, 2019)
This study attempts to build the Islamic leadership potential of groups of students by getting them to watch videos related to Sūrah Yasin throughout the semester. Based on the work of Argyris, it is argued that developing leaders requires double-loop learning. Delahaye called this questioning “paradynamic assumptions”. In this study, internalising the paradynamic assumptions of the Qur’ān is called Qur’ānic thinking. To develop Muslim leaders, it is assumed that by studying Sūrah Yasin, one can develop Qur’ānic thinking. This will lead to a growth-mindset, new assumptions about the knowledge of leadership and a new behaviour. To test this assumption, an action research approach was used with two groups of students at the International Islamic University Malaysia. Participants were asked to watch videos related to Sūrah Yasin throughout the semester. Sūrah Yasin was used because it encapsulates Qur’ānic thinking. These two experiments seemed successful and the lessons related to the experiments are explored.